2002
DOI: 10.1046/j.1463-1318.2002.00357.x
|View full text |Cite
|
Sign up to set email alerts
|

The outcome of surgery for complex anal fistula

Abstract: OBJECTIVE: The aim of this study was to examine the results of surgery for complex anal fistulas treated by a variety of techniques, in terms of fistula healing, recurrent anal sepsis and effect of surgery on anal continence. PATIENTS AND METHODS: This study included 63 patients with complex fistulas treated between November 1995 and September 1999. A variety of techniques were employed, including short-term loose seton drain (12), long-term loose seton drain (11), cutting seton (17), and rectal advancement fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 29 publications
(32 reference statements)
2
44
0
4
Order By: Relevance
“…26,27 The rationale for this is to facilitate drainage and thus avoid recurrent septic episodes and abscess formation. Our data, however, suggest that, while a loose seton does not involve sphincter division, there was no difference in QOL between patients with and without a seton, and no significant difference in urgency.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 The rationale for this is to facilitate drainage and thus avoid recurrent septic episodes and abscess formation. Our data, however, suggest that, while a loose seton does not involve sphincter division, there was no difference in QOL between patients with and without a seton, and no significant difference in urgency.…”
Section: Discussionmentioning
confidence: 99%
“…The main objective of surgery for an anal fistula is to eradicate the fistula tract while maintaining anal continence [25] .…”
Section: Discussionmentioning
confidence: 99%
“…Christensen et al [35] 13 ⁄ 21 Durgan et al [38] 2 ⁄ 10 Dziki and Bartos [39] 4 ⁄ 21 4 ⁄ 4 4⁄ 7 Fasth et al [40] 0 ⁄ 5 0⁄ 2 García-Aguilar et al [42] 8 ⁄ 12 Graf [44] 15 ⁄ 29 Gurer et al [25] 0 ⁄ 4 0⁄ 12 0 ⁄ 1 Hämäläinen and Sainio [45] 18 ⁄ 30 2 ⁄ 2 2⁄ 3 Hamel et al [46] 0 ⁄ 12 Hasegawa et al [48] 11 ⁄ 22 2 ⁄ 3 2⁄ 3 Joy and Williams [51] 5 ⁄ 10 McCourtney and Finlay [53] 3 ⁄ 16 Mentes et al [54] 4 ⁄ 20 Qureshi et al [57] 2 ⁄ 4 Tahir [58] 5 ⁄ 9 Tocchi et al [60] 4 ⁄ 28 Vatansev et al [61] 5 ⁄ 32 Walfisch et al [62] 0 ⁄ 23 Williams et al [63] 8 ⁄ 13 Zbar et al [22] 3 Despite the difficulty in comparing the different reports, this study has identified some important points. First the global rate of incontinence was 12% when any kind of cutting seton was used.…”
Section: Referencementioning
confidence: 99%
“…13 ⁄ 21 Cox et al [36] 4 ⁄ 8 Culp [26] 3 ⁄ 20 Decanini-Terán et al [37] 0 ⁄ 42 Deshpande et al [30] 0 ⁄ 397 Durgan et al [38] 2 ⁄ 10 Dziki and Bartos [39] 12 ⁄ 32 † Fasth et al [40] 0 ⁄ 7 Flich Carbonell et al [41] 3 ⁄ 19 García-Aguilar et al [42] 8 ⁄ 12 Gonzalez-Ruiz et al [43] 0 ⁄ 31 Graf et al [44] 11 ⁄ 29 4 ⁄ 4 Gurer ‡ et al [25] 0 ⁄ 17 Hämäläinen and Sainio [45] 22 ⁄ 35 Hamel et al [46] 0 ⁄ 12 Hammond et al [47] 4 ⁄ 16 Hasegawa et al [48] 15 ⁄ 28 Held et al [49] 0 ⁄ 9 Ho et al [20] 3 ⁄ 46 † Isbister and Al Sanea ‡ [50] 17 ⁄ 47 † Joy and Williams [51] 5 ⁄ 10 Malouf et al [52] 1 ⁄ 3 McCourtney and Finlay [53] 3 ⁄ 16 Mentes et al [54] 4 ⁄ 20 Misra and Kapur [55] 0 ⁄ 53 Mohite et al [31] 0 ⁄ 114 Pescatori et al [56] 3 ⁄ 17 Qureshi et al [57] 2 ⁄ 4 Shukla et al [21] 8 ⁄ 155 Tahir § [58] 5 ⁄ 9 Theerapol et al [59] 0 ⁄ 41 Tocchi et al [60] 4 ⁄ 28 Vatansev et al [61] 5 ⁄ 32 Walfisch et al [62] 0 ⁄ 23 Williams et al [63] 8 ⁄ 13 Zbar et al [22] 3 ⁄ 34 Average rates (%) 15.9% 100% 10.5%…”
mentioning
confidence: 99%